Fabrication of new cylinder head concept model for 4-stroke motorcycle engine - Carl-Ventolinson, Anak Emley (2008)
This project focuses on re-design and fabrication of new cylinder head concept model for a 4-stroke motorcycle engine. The idea of the new cylinder head model was also completed. It’s for the purpose of demonstrating the idea of this new concept. It also focuses on re-design the new upper piston for the new cylinder head. The piston based design was from PSM student. The re-design was done for simplifying the fabrication, machining and casting process. To achieve this project objective, this upper piston pattern should be fabricated using casting and machining process. But the dimension changes were done after the first casting work didn’t produce the desired product. This project flow must start from study, design, and lastly fabrication process. Before fabricate the upper piston, a study was made for the design based on the original design by Malcolm Beare and study on Modenas 110cc engine system. It is because to study the specification need and maintain the original design. Diploma Final Year Project will cover for the whole last semester, before go to the industrial training to complete this project. This is an individual task and must do by ourselves. This is also one of opportunity to student to show or to apply their knowledge also skill in using manufacturing process and mechanical design software in complete this project. Time management and a good planning also important to make sure the entire plan are in their way. Lastly, discipline needed to complete this project.